Lesson going digital: e-content of the current initiatives in environmental-related management accounting / Farra Azureen Johari ... [et al.] - Johari, Farra Azureen; Ahmad Sapari, Aina Najwa; Mohamad Ishak, Fatin Afrina; Abd Razak, Siti Noor Azmawaty (Universiti Teknologi MARA, Kedah, 2023)
Crisis requires society to renew itself, albeit in a disruptive way. The Covid-19 pandemic is transforming ways of teaching and learning on a global level, suddenly and dramatically. The higher education institutions are undergoing radical transformations driven by the need to digitalize education, teaching and learning processes with academics who lack innate technological capabilities for online teaching. The university system must strive to overcome this situation to be competitive and provide high-quality education in a scenario of digital transformation, disruptive technological innovations, and accelerated change. This e-content is part of the pilot project of digitalizing learning with regards to the subject Seminar in Management Accounting, a compulsory code taken by students in semester six in Bachelor in Accountancy, MARA University of Technology. The main objective of the e-content is to provide ease of access and encourage learning beyond classrooms borders as the e-content is able to be accessed by any students via any digital device such as android phones or laptop. As the contents of the lessons are rather theoretical based, this e-content endeavored a more interesting approach to gauge and sustain students’ attention via a less than 20 minutes slides show. This e-content is expected to benefit a few types of users. Firstly, the students. As learning become more flexible, it is hoped that it would enhance students’ understanding on the subject matter. Secondly, the educators themselves can use the e-content as part of their teaching aid. In the future, there might be more topics added to the e-contents hence fulfilling the commercialization potentials this product may have.